2019
DOI: 10.1002/anie.201901760
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible Heterogeneous MOF–Cu Catalyst for In Vivo Drug Synthesis in Targeted Subcellular Organelles

Abstract: As at ypical bioorthogonal reaction, the coppercatalyzedazide-alkyne cycloaddition (CuAAC) has been used for drug design and synthesis.H owever,f or localized drug synthesis,i ti si mportant to be able to determine where the CuAACr eaction occurs in living cells.I nt his study,w e constructed ah eterogeneous copper catalyst on am etalorganic framework that could preferentially accumulate in the mitochondria of living cells.Our system enabled the localized synthesis of drugs through as ite-specific CuAACr eacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
145
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 71 publications
(32 reference statements)
0
145
0
5
Order By: Relevance
“…46 In situ drug synthesis within living cells or organisms through targeted bioorthogonal catalysis may overcome the above mentioned drawbacks because it can greatly improve drug concentration at desired sites and reduce off-target effects. [47][48][49][50][51][52] We speculated that in situ drug synthesis through CuAAC reaction would probably mitigate the cytotoxicity caused by the Ab-Cu aggregates. Recent studies have indicated that the aggregation properties and cytotoxicity of Ab are closely related to the hydrophobicity of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…46 In situ drug synthesis within living cells or organisms through targeted bioorthogonal catalysis may overcome the above mentioned drawbacks because it can greatly improve drug concentration at desired sites and reduce off-target effects. [47][48][49][50][51][52] We speculated that in situ drug synthesis through CuAAC reaction would probably mitigate the cytotoxicity caused by the Ab-Cu aggregates. Recent studies have indicated that the aggregation properties and cytotoxicity of Ab are closely related to the hydrophobicity of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…[49] Another strategy is to increase the directional aggregation of copper ions near the azido and alkynyl groups, introduce chelating groups near the active center and reduce the concentration of copper ions. Zhu and co-workers reported that the method could significantly accelerate the copper-catalyzed cycloaddition by introducing pyridylmethyl azide (53) (Figure 9). [50] Ting's group developed a fast, cell-compatible click chemistry with copper-chelating azides for biomolecular labeling.…”
Section: Cu(i) Catalyzed Azido-alkynyl Cycloadditionsmentioning
confidence: 99%
“…[35] Recently,W ang et al reported a heterogeneous MOF-Cu catalyst that can target mitochondria and in situ synthesize drug by at ypical bioorthogonal CuAAC reaction. [36] Firstly,t he MOF scaffold was easily constructed by reactiono fZ rCl 4 and 2-aminoterephthalic acid. And then, coppern anoparticles were prepared and distributed on the MOF by Cu reduction (MOF-Cu).…”
Section: Intracellular Synthesismentioning
confidence: 99%
“…Recently, Wang et al. reported a heterogeneous MOF‐Cu catalyst that can target mitochondria and in situ synthesize drug by a typical bioorthogonal CuAAC reaction . Firstly, the MOF scaffold was easily constructed by reaction of ZrCl 4 and 2‐aminoterephthalic acid.…”
Section: Intracellular Synthesismentioning
confidence: 99%
See 1 more Smart Citation